ESR Studies of the Cu (II) Complexes with the ONS Chelating Schiff Bases - Jezierska, Julia (Asian Journal of Chemistry, 2010)
The interactions between Cu(II) complexes of tridentate Schiff bases containing the ONS donor atoms (condensation products of 2-hydroxyaryl aldehydes and thiosemicarbazides or o-aminothiophenol) and molecules of polar solvents have been ESR studied both in liquid and in frozen solutions. On the basis of the ESR copper hyperfine structure parameters and the nitrogen superhyperfine splittings the presence of two different adducts with nitrogen coordinating solvents has been established and the structure of the adducts depending on the ligand nature has been discussed.